2020
DOI: 10.1155/2020/9152369
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Tasks-Based Optimal Filter Selection: An fNIRS Study

Abstract: Functional near-infrared spectroscopy (fNIRS) is one of the latest noninvasive brain function measuring technique that has been used for the purpose of brain-computer interfacing (BCI). In this paper, we compare and analyze the effect of six most commonly used filtering techniques (i.e., Gaussian, Butterworth, Kalman, hemodynamic response filter (hrf), Wiener, and finite impulse response) on classification accuracies of fNIRS-BCI. To conclude with the best optimal filter for a specific cortical task owing to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…Given that the motor task was performed in a stationary seated position, we did not expect any significant physiological influences associated with heartbeat, respiration, or blood pressure fNIRS signal. While there currently is no consensus on fNIRS data preprocessing for neuroimaging (Pfeifer et al, 2018;Klein and Kranczioch, 2019), a number of approaches have been proposed in the literature to reduce fNIRS signal contamination of cortical hemodynamic activity (Scholkmann et al, 2014;Khan et al, 2020) including bandpass filtering (Naseer and Hong, 2015;Kamran et al, 2016). The absence of bandpass filtering of the present fNIRS data does not allow us to rule out physiological noise as potentially contributing to our reported findings.…”
Section: Limitationsmentioning
confidence: 83%
“…Given that the motor task was performed in a stationary seated position, we did not expect any significant physiological influences associated with heartbeat, respiration, or blood pressure fNIRS signal. While there currently is no consensus on fNIRS data preprocessing for neuroimaging (Pfeifer et al, 2018;Klein and Kranczioch, 2019), a number of approaches have been proposed in the literature to reduce fNIRS signal contamination of cortical hemodynamic activity (Scholkmann et al, 2014;Khan et al, 2020) including bandpass filtering (Naseer and Hong, 2015;Kamran et al, 2016). The absence of bandpass filtering of the present fNIRS data does not allow us to rule out physiological noise as potentially contributing to our reported findings.…”
Section: Limitationsmentioning
confidence: 83%
“…In the literature, researchers used mental arithmetic, visual tasks, letter padding, word generation, object rotation, motor imagery, motor execution, and music imagery as brain activities for data acquisition for fNIRS-BCI [22,40,[46][47][48][49]. In this study, motor imagery of left-and right-hand and mental arithmetic were selected as the brain activities.…”
Section: Experimental Paradigm/protocolmentioning
confidence: 99%
“…Various noises like instrumental, physiological, and experimental noises contained by acquired hemodynamic signals had to be removed before feature extraction and classification [49]. Following the instructions [45] about preprocessing, ∆HbO and ∆HbR data were band-pass filtered using a fourth-order Butterworth filter with a passband of 0.03-0.15 Hz to remove physiological noises.…”
Section: Signal Processingmentioning
confidence: 99%
“…A systematic review of filtering methods in adult NIRS studies ( Pinti et al, 2019 ) compared Infinite Impulse Response (IIR) and Finite Impulse Response (FIR) filters of different orders, and found that high order (>500) bandpass FIR filters perform best. When filters were compared in terms of their impact on classification performance in a Brain-Computer Interface study, the hemodynamic response filter ( Penny et al, 2011 ) was found to work best ( Khan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%